Fabrication-tolerant active-passive integration scheme for vertically-coupled microring resonators - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2006)
The large-scale photonic integration of microring resonators in three dimensions made possible by recent developments in vertical coupling and wafer bonding technology is shown to be sensitive to lateral mask misalignment for the ring and bus waveguides introduced during the fabrication process. For a typical 20-μm radius, vertically coupled microring calculations reveal a linear relationship between deviation in the coupling coefficient and lateral misalignment. A coupling coefficient reduction of 50% is predicted for a lateral misalignment of 0.3 μm, which is typical for an alignment accuracy limited by the current state-of-the-art mask alignment process. The use of a wide multimode bus waveguide is proposed to ameliorate this alignment sensitivity. The mode-expanded bus waveguide, together with its physically wider structure, reduces the dependence of modal overlap and coupling length on precise alignment, resulting in significantly relaxed fabrication tolerance. Deviation of coupling coefficient decreases by an order of magnitude for the new ring coupler geometry, where a sole reduction of 5% is obtained for the same amount of misalignment. The implications of the proposed structure are subsequently investigated for microring laser performance. The differential slope efficiency is shown to be at least five times less sensitive to lateral misalignment for the proposed structure within a small misalignment regime. This readily adaptable coupler geometry based on existing vertical coupling architectures is transferable to any fabrication scheme with multiple waveguide layers coupled vertically, and is of particular importance to microring resonators with small radii.